“Making Myself”: An Exploratory Study of Black Christian Childfree Women’s Concepts of Family - Moultrie, Monique Nicole (Journal of religious ethics, 2021)
In this article, I utilize Black queer feminist ethicist Thelathia “Nikki” Young’s concept of subversive and generative moral imagination and queer relationality to explore the concept of family for Black Christian women who are childfree by choice positing that these women have a nuanced understanding of legacy, nurturing, and family that is greatly influenced by Christian (and particularly Black Protestant) norms. First, I present the scholarship on childlessness, providing keen attention to how this literature is racialized and gendered in a heteronormative manner. In the second section, themes are explored from the focus group interviews conducted with nine Black Christian childfree women. Finally, the essay ends by providing constructive ethical practices for Black religious communities and the sub-discipline of reproductive ethics. This exploratory research begins the work of investigating how Black women make themselves over as participants in new familial structures that are not contingent upon reproduction and biology.